A Comparison of the Effects of Short-term Singing, Exercise, and Discussion Group Activities on the Emotional State and Social Connectedness of Older Australians. (26th September 2018) - Maury, Susan; Rickard, Nikki
Choir membership has been shown to improve emotional states and facilitate social connectedness. It is, however, less clear whether these benefits are unique to group singing or are shared by other social group activities that include some of the characteristics of choirs other than singing, such as music listening and social interaction. This research compares older Australians who are members of either a choir that both produces and listens to music in a social context, an exercise group that incorporates music listening and movement with social interaction, or a current events discussion group with social interaction but no music content. Participants were administered emotional state and cohesion questionnaires at two test times, just prior to and immediately after the session, to determine the short-term (60–90 minutes) effects on emotional state and social cohesion as result of different social activities containing varying levels of music engagement. A two-way Analysis of Variance (ANOVA) revealed significant improvements in positive affect and cohesion scores, and a decrease in negative affect and tiredness scores, over time for all groups. The choir and exercise groups were also observed by two raters who recorded observable behaviors categorized using the circumplex model of emotion. Findings revealed that both groups demonstrated significant increases in Activated Pleasant (high positive affect, high arousal) behaviors over time, but with no differences between the two groups. Taken together, these studies suggest that well-being benefits are shared by self-selected leisure social group activities, and that the effects can be observed within a very short time frame using both self-report and behavioral measures. The authors suggest that future research incorporates suitable control groups into research designs to better articulate any unique benefits that group singing may confer.